Efficacy of Fungicidal Formulations along with Botanicals and Bio-Control Agents against Wheat Spot Blotch (Bipolaris sorokiniana) under Laboratory and Field Conditions - Poudel, Ritu Rani; Yadav, Ritesh Kumar; Manandhar, Hira Kaji; Shrestha, Sundar Man (Journal of Agriculture and Forestry University, 2025)
The present investigation was conducted to identify suitable fungicide formulation along with botanicals and bio-control agents (BCAs) against spot blotch disease (Bipolaris sorokiniana) under laboratory and field conditions. To test the fungi toxicity laboratory experiment (in-vitro) was conducted using fungicides (nine) and BCA (two) at different levels of concentrations following the poisoned food technique. Similarly, A field experiment was conducted to test the efficacy of fourteen disease-controlling agents (fungicides, botanicals, and BCAs) under natural epiphytotic conditions for spot blotch of wheat (variety-Gautam). Under in-vitro conditions, fungicides Nativo 75WG (trifloxystrobin 25% + tebuconazole 50%), DILT (propiconazole 25% EC), and ZOLE PLUS (hexaconazole 5% SC) were highly effective against the mycelia growth of spot blotch fungi in all the concentrations (25, 50 and 100 mg/L). Likewise, under epiphytotic conditions highest efficacy against spot blotch as lower percent disease control (PDC) was observed as 75.41% followed by 74.60 % and 68.32 % in the plot having seed treated with Vitavax and plants sprayed with Nativo 75WG (trifloxystrobin 25% +tebuconazole 50%) followed by plot having seed treated with Vitavax and plants sprayed with DILT (propiconazole 25% EC) and plots having seed treated with Vitavax and plants sprayed with ZOLE PLUS (hexaconazole 5% SC), respectively. The present study showed that seed treatment with Vitavax followed by the spraying one of the following fungicides, i.e., Nativo 75WG, DILT, and ZOLE PLUS @ 0.05, 0.1, and 0.1 % respectively could be effective for the management of spot blotch in wheat.